Role of the Aceh government in managing foreign labour - Nasrianti Razaly; Muhibuddin Muhibuddin (Geuthèë Institute, Aceh, 2023)
The 1945 Constitution, Article 27 Paragraph stated that “every citizen has the right to work and a decent living for humanity